RE-DESAIN BUKU PANDUAN PRAMUKA UNTUK ANAK SEKOLAH DASAR - M. ZIKRI HANIF, Hendra Afriwan, S.Sn., M.Sn., Dr. M. Nasrul Kamal, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Scouting is essentially an educational activity carried out outside the school campus and family education environment under the responsibility of adult members, with the principle of scouting, an important aim in education that is fun for young people with values based on Satya and Darma Pramuka.The Book of Scout Guides for Elementary School is designed as a design solution for students who are doing scouting activities. This book is re-designed using illustrations, text, colors, and attractive layouts to suit the characteristics of children. The data analysis in the design of Scout Guidebook for Elementary School was carried out by SWOT analysis through data collected and observations to the Quartir of the West Sumatra Regional Scout Movement, Padang State University Scout Activity Unit, and several Pandega, Trustees.The purpose of the re-design of this scout guide book was to produce a scout guide book for elementary school children and presented in an interesting and communicative manner with illustrations of different Indonesian scout characters with other scout book illustrations, as well as information about personality education, personality formation activities, skills, and noble character of scouts. The presentation of information on scout guide books for elementary school children with this design is expected to increase the knowledge of scout alert students and provide benefits in scouting activities.In addition to the Re-design of the Book of Scout Guides for Primary School, supported by several media as the main media, this design includes other posters, x-banners, stickers, pencil boxes, drinking bottles, and food boxes as supporting media books and as promotional media.Keywords: Re-design Scout Handbook, For Elementary School, Illustration